Flap Selection Algorithm Based on the Body Mass Index for Phalloplasty in Female-to-Male Transgender: Techniques and Outcomes - Watanabe, Toshiyuki; Namba, Yuzaburo; Kimata, Yoshihiro (Journal of Reconstructive Microsurgery Open, 2021)
Background Various phalloplasty methods have been reported; however, a consensus has not been reached. Therefore, we suggest an alternative algorithm for an ideal phalloplasty considering the factors that affect flap selection.Methods We retrospectively examined 32 phalloplasty cases of female-to-male transgender. Flaps used for phalloplasty were classified into three groups as follows: (1) radial forearm (RF) group, (2) anterolateral thigh (ALT) group, and (3) flap combination (FC) group. Statistical analyses were performed to determine the significance of age and body mass index (BMI) as well as differences in the rates of postoperative complication, reoperation, esthetic acceptability, tactile or erogenous sensibility, and the ability to urinate while standing.Results Ten cases were included in the RF group and 7 and 15 cases in the ALT and FC groups, respectively. With respect to BMI, the RF group (mean [standard deviation (SD)] = 25.9 [3.3]) showed significantly higher BMI than the ALT (21.7 [0.9]) or FC group (22.2 [4.5]). The RF (mean [SD] = 3.7 [0.4]) and ALT groups (3.5 [0.9]) had significantly higher esthetic acceptability evaluation scores (from 1 to 4) than the FC group (2.5 [1.2]). Moreover, the RF and ALT groups were superior than the FC group in terms of tactile or erogenous sensibility rates.Conclusion BMI effected flap choices for phalloplasty because of the correlation between BMI and skin thickness. FC becomes an option between ALT flap and RF flap in terms of flap choice based on BMI. Our alternative algorithm for an ideal phalloplasty based on BMI will be useful for objective flap choices.
Keywords: body mass index; phalloplasty; female-to-male transgender